Kolaborasi Multi-aktor dalam Ekowisata Mangrove: Transformasi Sosial dan Ekonomi Berbasis Komunitas di Desa Waiheru, Maluku - Rusli, Arisnu Arief; Tuanaya, Wahab; Fretes, Judy de (Universitas Pattimura, 2023)
Community-based ecotourism has become a potential strategy for supporting sustainable development, particularly in coastal areas. This study aims to analyze the dynamics of multi-actor collaboration in the development of mangrove ecotourism in Waiheru Village, Maluku, and its impact on the social and economic transformation of the local community. The research employs a qualitative approach, utilizing data collection techniques such as in-depth interviews, participatory observation, and document analysis. The findings indicate that the development of mangrove ecotourism in Waiheru Village involves three key actors: the village government, local Micro, Small, and Medium Enterprises (UMKM), and youth organizations under Karang Taruna. The collaboration among these actors has led to significant social changes, including increased community awareness of mangrove conservation and the emergence of local initiatives in ecotourism management. Economically, ecotourism development has created new business opportunities for the community, increased income through the tourism sector, and encouraged economic diversification within the village. The novelty of this study lies in identifying effective patterns of multi-actor collaboration within the context of community-based ecotourism, which can serve as a model for other regions with similar potential. This study recommends policies that support the sustainability of community-based ecotourism, capacity-building initiatives for local communities in ecotourism management, and the strengthening of synergy between the government, private sector, and local communities to ensure the long-term benefits of mangrove ecotourism. With a holistic and participatory approach, ecotourism can become a vital instrument for enhancing community welfare while preserving coastal ecosystems.